Technical Analysis Using 100 Percent Palm Kernel Shell as Fuel in Circulation Fluidized Bed Boiler Type - Masrajuddin; Sudiarto, Budi; Setiabudy, Rudy (Universitas Indonesia, 2024)
Energy is a basic human need that has increased in use. Given the limited energy resources, it is necessary to manage energy appropriately and efficiently. Energy efficiency not only has an impact on reducing production costs, but also on reducing emissions. As a concrete step to support the government's net zero emission program by 2060, the company is trying to use alternative biomass fuels, namely: palm kernel shell. The purpose of this study is to conduct a technical and economic analysis of the use of 100 percent palm kernel shells as fuel in a circulation fluidized bed boiler type power plant. This research was conducted at power plant unit 2 of PT XYZ, located in Cilegon, Banten Province. The parameters measured are limited to boiler efficiency, thermal efficiency, and heat rate. The results showed that when using palm kernel shells, boiler efficiency decreased 0.47 percent, thermal efficiency decreased 0.24 percent, and heat rate increased 22 kcal/kWh or 0.76 percent. By considering of three operational parameters (boiler efficiency, thermal efficiency, and heat rate) it can be concluded that technically the use of 100 percent palm kernel shells as fuel in the plant is feasible. There is no major impact on boiler performance regarding the transition of coal to palm kernel shells. The impact of long-term use of palm kernel shells on equipment is beyond the scope of this research.